Can you find the relation between 1007 and 2015?

Algebra Level 4

r = 1 1007 c o s ( 2 π r 2015 ) \sum ^{1007} _{r=1} cos(\frac{2 \pi r}{2015}) can be expressed as ( m n ) (-\frac{m}{n}) , where m m and n n are co-prime positive integers. Calculate m + n m+n .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Arpon Paul
Dec 3, 2015

Suppose, x 2 m + 1 a 2 m + 1 = 0 x^{2m+1}-a^{2m+1}=0 ... ... ... (i)

( x a ) ( x 2 m + a x 2 m 1 + a 2 x 2 m 2 + . . . + a 2 m ) = 0 \implies (x-a)(x^{2m}+ax^{2m-1}+a^2 x^{2m-2}+ ... +a^{2m})=0

x = a \implies x=a , or , x 2 m + a x 2 m 1 + a 2 x 2 m 2 + . . . + a 2 m = 0 x^{2m}+ax^{2m-1}+a^2 x^{2m-2}+ ... +a^{2m}=0 ... ... ...(ii)

Again, from (i),

x 2 m + 1 = a 2 m + 1 x^{2m+1}=a^{2m+1}

x 2 m + 1 = a 2 m + 1 exp ( i 2 π r ) \implies x^{2m+1}=a^{2m+1} \exp(i \cdot 2\pi r) [ r r is an integer]

x = a exp ( i 2 π r 2 m + 1 ) \implies x=a \exp(i \cdot \frac{ 2\pi r}{2m+1})

x = a [ cos ( 2 π r 2 m + 1 ) + i sin ( 2 π r 2 m + 1 ) ] \implies x=a[ \cos (\frac{ 2\pi r}{2m+1})+i \sin (\frac{ 2\pi r}{2m+1})]

x a cos ( 2 π r 2 m + 1 ) = i a sin ( 2 π r 2 m + 1 ) \implies x-a \cos (\frac{2\pi r}{2m+1})= i a \sin(\frac{ 2\pi r}{2m+1})

x 2 2 a x cos ( 2 π r 2 m + 1 ) + a 2 cos 2 ( 2 π r 2 m + 1 ) = a 2 sin 2 ( 2 π r 2 m + 1 ) \implies x^2-2ax \cos (\frac{2\pi r}{2m+1}) +a^2 \cos ^2 (\frac{2\pi r}{2m+1}) = -a^2 \sin ^2 (\frac{2\pi r}{2m+1}) [we can square the previous equation without having irrelevant root. The reason is, the reverse process gives us two equations, and both of them are valid for two different values of r r ]

x 2 2 a x cos ( 2 π r 2 m + 1 ) + a 2 = 0 \implies x^2-2ax \cos (\frac{2\pi r}{2m+1}) +a^2=0

If r = 0 r=0 , then x = a x=a .

We have m m numbers of quadratic equations by putting r = 1 , 2 , 3... m r=1, 2, 3 ... m , and the 2 m 2m numbers of roots of these equations are also the roots of the following 2 m 2m degree polynomial equation ( from (ii) ), x 2 m + a x 2 m 1 + a 2 x 2 m 2 + . . . + a 2 m = 0 x^{2m}+ax^{2m-1}+a^2 x^{2m-2}+ ... +a^{2m}=0

So, x 2 m + a x 2 m 1 + a 2 x 2 m 2 + . . . + a 2 m = r = 1 m [ x 2 2 a x cos ( 2 π r 2 m + 1 ) + a 2 ] x^{2m}+ax^{2m-1}+a^2 x^{2m-2}+ ... +a^{2m}= \prod ^m _{r=1} [x^2 - 2ax \cos (\frac{2\pi r}{2m+1})+a^2]

Equating the the coefficient of x 2 m 1 x^{2m-1} on both sides,

2 r = 1 m cos ( 2 π r 2 m + 1 ) = 1 -2 \sum _{r=1} ^{m} \cos (\frac{2\pi r}{2m+1}) = 1

r = 1 m cos ( 2 π r 2 m + 1 ) = 1 2 \implies \sum _{r=1} ^{m} \cos (\frac{2\pi r}{2m+1}) = -\frac{1}{2}

Aditya Dhawan
Nov 8, 2016

I n g e n e r a l , r = 1 n cos 2 π r 2 n + 1 = 1 2 { 2 cos 2 π r 2 n + 1 = ω r + ω r r = 1 n cos 2 π r 2 n + 1 = r = 1 2014 ω r 2 = 1 2 } In\quad general,\quad \sum _{ r=1 }^{ n }{ \cos { \frac { 2\pi r }{ 2n+1 } } } =\quad \frac { -1 }{ 2 } \\ \left\{ \because \quad 2\cos { \frac { 2\pi r }{ 2n+1 } =\quad { \omega }^{ r } } +\quad { \omega }^{ -r }\\ \Rightarrow \sum _{ r=1 }^{ n }{ \cos { \frac { 2\pi r }{ 2n+1 } } } =\quad \frac { \sum _{ r=1 }^{ 2014 }{ { \omega }^{ r } } }{ 2 } \quad =-\frac { 1 }{ 2 } \right\}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...